Comparison of electrolyte and mineral water intake on heart rate recovery during high-intensity exercise - Handayani Handayani; Y. Touvan Juni Samodra; Asry Syam (Sriwijaya Journal of Sport, 2026)
Research Background: Fluid deficiency or dehydration can negatively affect health and physical performance, including reduced blood volume and electrolyte imbalance. This condition may influence cardiovascular responses, particularly heart rate, during high-intensity physical activity. Therefore, maintaining fluid balance through the consumption of mineral water and electrolyte beverages is important to sustain performance and accelerate body recovery after physical activity. Research Objectives: This study aimed to analyze the differences in the effects of electrolyte fluids and mineral water on heart rate following high-intensity physical activity. Method: This study employed an experimental method with a two-group treatment design. The participants consisted of 18 sports students divided into two groups: the electrolyte fluid group and the mineral water group. Each group was given 240 ml of beverage before performing three repetitions of 400-meter running. Heart rate measurements were taken for 10 seconds after each 400-meter run session. Data were analyzed using a comparative test to determine differences in heart rate responses between the two groups. Results: The results showed differences in heart rate between the group consuming electrolyte fluids and the group consuming mineral water after three repetitions of 400-meter running. Based on the mean post-exercise heart rate values, the group consuming mineral water demonstrated lower heart rates compared to the group consuming electrolyte fluids. This finding indicates that heart rate recovery in the mineral water group occurred more rapidly. Conclusion: Mineral water was more effective than electrolyte fluids in supporting heart rate recovery after high-intensity physical activity. These findings suggest that mineral water consumption may serve as a better hydration strategy for accelerating cardiovascular recovery during high-intensity exercise.